MODIFIKASI DAN PEMBUATAN ALAT PENJERNIH AIR MODERN KONSUMSI RUMAH TANGGA - Zulkarnain Fatoni; M Lazim (Universitas Tridinanti Palembang, 2018)
Modern Water Purifier uses the main drive, namely a water pump with a power of 15-30 watts, a voltage of 220 volts AC, a frequency of 60 hertz with an absolute pressure from the pump 10-100 psi (Pond Square In). The working principle of this equipment is the water pump as the main water drive or diverter that is connected with filters which then will flow through the hose which then comes out through holes (pores) that are on the sides of the filter. From the water that comes out it will go to the Reverse Osmosis (RO) membrane and then it will flow towards Bio Ceramics which will last through Post Carbon so that the water that comes out after the process will become water that can be consumed by humans. With the price of R ranging from 0 ÷ 1, it can be seen that water that has been processed with a yield of 0.9 can be said to be feasible to drink or contaminant substances in water are perfectly retained by the membrane. Keywords: Membrane, Reverse Osmosis (RO), Bio Ceramics, Post Carbon